DO INTERNET MARKETING FACTORS WITH ISLAMIC VALUES IMPROVE SME PERFORMANCE? - Rizaldi Yusfiarto; Galuh Tri Pambekti (Journal of Islamic Monetary Economics and Finance, 2019)
Internet marketing is regarded as the right business strategy for small and medium- sized enterprises (SMEs) in the current revolutionary era. This study aims to determine the impact of internet marketing factors on improving the business performance of SMEs using the Islamic perspective. Specifically, the aim of this study is to examine how the influence of landing pages, search engine optimisation and customer databases affects SME performance through internet marketing with Islamic values. Statistical testing was undertaken to build and test statistical models in the form of causal models, along with factor analysis, path analysis and regression. The analysis was therefore undertaken using the structural equation modelling (SEM) approach. The research project was conducted among the internet marketer community in Indonesia, with a sample of 245 business units based on the desired criteria. Analysis of the research results shows that the hypotheses in this study as a whole are accepted, from which it can be concluded that a business strategy that uses a combination of internet marketing aspects and Islamic perspectives can be a competitive advantage. This is especially true in the aspects of building consumer trust, categorising consumer preferences specifically and producing broad customer relationship solutions.